DEVELOPMENT STRATEGIES OF SMALL AND MEDIUM ENTERPRISES IN THE FOOD INDUSTRY AND THEIR ROLE IN THE NATIONAL ECONOMY (Web of Teachers: Inderscience Research, 2026)
Small and medium enterprises hold a vital place in the modern food industry. These businesses serve as a foundation for economic progress and innovation, forming a bridge between rural areas and urban markets. The ever-changing marketplace, influenced by new technologies and shifting consumer behaviors, brings both opportunities and challenges. This essay explores the development strategies for small and medium enterprises within the food sector and analyzes their importance in strengthening national economies, while offering insights for policy and practice.